VD_FINDINFO Arrêt / 2013 / 551 vom 12. September 2013 - VD Tribunal cantonal (2013)
DÉFAUT ESTHÉTIQUE, OPÉRATION, GARANTIE DE PRISE EN CHARGE, RAPPORT MÉDICAL | 25 al. 1 LAMal, 25 al. 2 let. a LAMal, 32 al. 1 LAMal, 33 LAMal, 3 LPGA, 33 OAMal